Law of dismissal in Malaysia / Hanan Othman - Othman, Hanan (Faculty of Law, 1986)
In the practice of Industrial Relation , there are different modes by which relationship between the worker and the employer is suspended. Sometimes this relationship is suspended on the initiative of the workers. Dismissal of an employee is one of the fundamental moues by which the employer and employee relationship stands stagnant. It is distinguishable from termination In labour law practises, termination of services has a very general significance. The phrase simply meant to say that the services of the employee are brought to an end. Under common law governing the relation of employers and employees , an employer is entitled to terminate the services of his employee at any time subject to customary notice unless under a binding contract security of tenure of service is granted. An employer cannot normally be compelled to retain an employee when he does not desire to retain in his employment. Certain statutory provisions have however been made which have considerabbly altered the Common Law rule governing the relations of an employer and an employee. And under statutory provisions this right has been restricted to a certain extent..